Generation of femtosecond electron and photon pulses - C. Thongbai (2018)
Femtosecond (fs) electron and photon pulses become a tool of increasing importance to study dynamics in ultrafast processes. Such short electron pulses can be generated from a system consisting of a thermioniccathode RF-gun and a magnetic bunch compressor. The fs electron pulses can be used directly or used as a source to produce equally short electromagnetic radiation pulses via certain kind of radiation production processes. At the Fast Neutron Research Facility (FNRF), Thailand, we are especially interested in production of radiation in Far-infrared and X-ray regime. In the far-infrared wavelengths, the radiation emitted from fs electron pulses is emitted coherently resulting high intensity radiation. In the X-ray regime, development of fs X-ray sources is crucial for application in ultrafast sciene. © 2005 IEEE.